Investigation on adhesion force of TBAB hydrate to cooling copper surface. (June 2017) - Matsumoto, Koji; Murase, Masashi; Ehara, Kohei; Sakamoto, Junki; Ueda, Jun
Highlights: Shearing stress of TBAB hydrate to copper increased with drop in surface temperature. The shearing stress did not depend on the type of TBAB hydrate crystal. The shearing stresses below 40 wt% were just nominal values because of free water. Appropriate shearing stresses were 0.76 (3 °C)and 0.73 MPa (5 °C). Both shearing stresses were approximately nine times that of ice at −3 °C. Abstract: When ice slurry is employed for air conditioning, there is gap of 5–7 °C between the melting point of the ice and the cooling water temperature. However, TBAB hydrate slurry made from an aqueous TBAB solution can remove the gap because it has a more suitable melting point. Furthermore, the slurry is relatively a high latent heat of fusion and good fluidity. So, the slurry is the most promising material for air conditioning. However, it is expected that TBAB hydrate in the slurry strongly adheres to surface of a metal such as copper. However, to date, there have been no quantitative studies of the adhesion forces, so in the present work adhesion forces of TBAB hydrates to copper surface at 3 and 5 °C were measured varying TBAB solution concentrations. And the adhesion force and its surface temperature-dependency were investigated based on surface energies and observations of hydrates crystals.